2016
DOI: 10.1002/mus.25184
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the motor unit behavior of lumbar erector spinae muscles through surface EMG decomposition technology in healthy female subjects

Abstract: This technique may further our understanding of individuals with back pain and other underlying neuromuscular diseases. Muscle Nerve 55: 28-34, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…During an 80% of maximum isometric contraction all motor units of the back-extensor muscles are assumed to be active. As the fatigue-related changes are preferably mediated by the slowing of the muscle fiber conduction velocity of fast fatiguing, higher threshold motor units, these flatter MF-SEMG slopes in seniors most likely arose from a proportionally smaller number of fast fatiguing muscle fibers [24,25], indicative of less glycolytic activity in these muscles. Such decline in muscle glycolytic activity likely results from neuronal incomplete regenerative mechanisms following axonal loss of higher threshold motor units with advancing age [8,9,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…During an 80% of maximum isometric contraction all motor units of the back-extensor muscles are assumed to be active. As the fatigue-related changes are preferably mediated by the slowing of the muscle fiber conduction velocity of fast fatiguing, higher threshold motor units, these flatter MF-SEMG slopes in seniors most likely arose from a proportionally smaller number of fast fatiguing muscle fibers [24,25], indicative of less glycolytic activity in these muscles. Such decline in muscle glycolytic activity likely results from neuronal incomplete regenerative mechanisms following axonal loss of higher threshold motor units with advancing age [8,9,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…and has been used in various applications [39][40][41][42]. For each MU, the decomposition outputs a MUAP recorded from each of the 4 channels, and a vector of time stamps when the MU fired.…”
Section: Data Processing 251 Decomposing and Validating Motor Unitsmentioning
confidence: 99%
“…For each MU, the decomposition outputs a MUAP recorded from each of the 4 channels, and a vector of time stamps when the MU fired. In addition to retaining MUs with accuracy greater than 90% accuracy by the algorithm output, as done in [39][40][41][42], valid MUs were retained via a 2-step spike-triggered averaging (STA) procedure described previously [29]. The first step averages raw EMG across all spikes in the trial in an 80 ms window centered at the spike time to isolate the MUAP in the EMG signal.…”
Section: Data Processing 251 Decomposing and Validating Motor Unitsmentioning
confidence: 99%
“…Recent studies have shown the utility of decomposition EMG to directly measure the motor unit behavior which may yield more information on any possible activation deficits in the LM. 43…”
Section: Study Limitationsmentioning
confidence: 99%